2019
DOI: 10.1016/j.scitotenv.2018.12.312
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic co-composting degradation of highly PCDD/F-contaminated field soil. A study of bacterial community

Abstract: Aerobic co-composting degradation of highly PCDD/F-contaminated field soil. A study of bacterial community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Therefore, to identify the potential microbial groups associated to PCDD/F degradation in our aged contaminated soil, the amplicon sequencing data were examined. So far, numerous bacterial at the family level Sphingomonadaceae and Bacillaceae-related populations have been associated with the degraders of PCDD/F and similar pollutants in contaminated soils [69,70]. Our findings showed that the abundance of Alicyclobacillaceae, Bacillaceae, Caulobacteraceae, Chitinophagaceae, Cytophagaceae, Sphingomonadaceae, and Xanthomonadaceae increased significantly in the Fm+RW1+Rh+µb condition compared to the non-vegetated one.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, to identify the potential microbial groups associated to PCDD/F degradation in our aged contaminated soil, the amplicon sequencing data were examined. So far, numerous bacterial at the family level Sphingomonadaceae and Bacillaceae-related populations have been associated with the degraders of PCDD/F and similar pollutants in contaminated soils [69,70]. Our findings showed that the abundance of Alicyclobacillaceae, Bacillaceae, Caulobacteraceae, Chitinophagaceae, Cytophagaceae, Sphingomonadaceae, and Xanthomonadaceae increased significantly in the Fm+RW1+Rh+µb condition compared to the non-vegetated one.…”
Section: Discussionmentioning
confidence: 56%
“…Rapid degradation of PCDD/Fs correlated with bacterial growth. Also, Huang et al (2019) monitored the degradation of PCCD/Fs-contaminated soil and bacterial communities during aerobic food waste co-composting, Though the microflora was largely dominated by the Firmicutes, other prominent phyla are Actinobacteria, Proteobacteria, and Bacteroidetes, while Bacillus was the dominant genus with consequent 75% degradation of toxic equivalent quantity.…”
Section: Dioxin Degraders As Candidate Organisms For Bioremediationmentioning
confidence: 99%
“…Kong, Li, Li, Wu, Zhang, and Li (2019) reported that N,N-dimethylformamide (DMF) was effectively degraded by aerobic activated sludge, but not the anaerobic digested sludge, due to the lack of DMF-hydrolyzing bacteria in the anaerobic sludge. Huang, Ngo, et al (2019) reported that aerobic co-composting with food waste significantly removed polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) in soils. Proteobacteria, Actinobacteria, Bacteroidetes, and Firmicutes were the major phyla of the bacterial community.…”
Section: Biological Treatmentmentioning
confidence: 99%
“…Huang, Ngo, et al (2019) reported that aerobic co‐composting with food waste significantly removed polychlorinated dibenzo‐p‐dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) in soils. Proteobacteria , Actinobacteria , Bacteroidetes , and Firmicutes were the major phyla of the bacterial community.…”
Section: Biological Treatmentmentioning
confidence: 99%